Emergency response: Effect of human detection resolution on risks during indoor mass shooting events. (April 2019) - Cho, Chunhee; Park, JeeWoong; Sakhakarmi, Sayan
Highlights: We developed an integrate approach for mass shooting analysis. We investigate the effect of human tracking/monitoring data on fatalities. Our approach showed the potential to identify a safety mechanism for evacuation. Abstract: During an emergency, people rely on a few behavioral rules to save themselves. However, these rules may not be reliable, especially in indoor environments, as they are not fully aware of site information and their ability to think properly becomes fragile. Despite the increasing occurrence of mass shootings, there is no advanced systematic mechanism, which leverages recent technological advancements, in place to save people from this terror. To overcome these challenges, this research explores an integrated approach by combining resources (human monitoring; building information; and agent-based modeling). This research is to ameliorate public safety by investigating mass shooting scenarios through integration. Specifically, this study unveils the effect of sensory data on fatalities, along with safety mechanisms offered by systematic action plans. We designed six scenarios by varying spatial sensing coverage (comprehensive visual representation of the situation) from 0% to 100%. Each scenario was tested from 2000 to 2500 times to obtain statistical significance. Results indicate that even low sensing coverages (20% and 40%) show a slight improvement for safe evacuation and clear potential to reduce casualties within the first five minutes. Significant improvements are found in all cases (safe evacuation, casualties, rescuing people, and total survival) when the sensing coverages are high, around 60% to 100%. This study confirms the applicability of an integrated approach to identify a safety mechanism operating in place during a mass shooting incident. The findings could serve as a basis for future studies that can progressively improve emergency safety mechanisms based on available site resources.